2016
DOI: 10.1111/jam.13001
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological characterization using combined culture dependent and independent approaches of Casizolu pasta filata cheese

Abstract: This study shows the first data on microbial groups and species involved in the manufacture of Casizolu cheese and highlights the role of Lact. paracasei and Enterococcus spp. from the earliest stages of ripening cheese; furthermore, provides evidence that raw milk cheese is a source of new strains and therefore a reservoir of microbial biodiversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 83 publications
2
14
0
4
Order By: Relevance
“…According to Carafa et al , the great number of singletons accounts for a high microbial biodiversity. Further, a similar number of singletons has been determined in cereals as well as in other food matrices . The 16S rDNA sequencing of representative isolates from each cluster identified 40 strains at the genus level and 11 strains at the species level.…”
Section: Resultsmentioning
confidence: 83%
“…According to Carafa et al , the great number of singletons accounts for a high microbial biodiversity. Further, a similar number of singletons has been determined in cereals as well as in other food matrices . The 16S rDNA sequencing of representative isolates from each cluster identified 40 strains at the genus level and 11 strains at the species level.…”
Section: Resultsmentioning
confidence: 83%
“…According to Mangia et al . cluster analysis of rep‐PCR banding profiles grouped their isolates of the same species into the same cluster. The 16S rDNA sequencing of representative isolates from each cluster allowed the identification of 35 colonies at species level.…”
Section: Resultsmentioning
confidence: 99%
“…However, in some cases, there was a different genetic profile for strains isolated from these different food matrices, such as clusters 23 and 75 being more typical of the barley, and clusters 1 and 2 more typical of the malt. According to Mangia et al (17) cluster analysis of rep-PCR banding profiles grouped their (25) reported that Staphylococcus spp. was among the main components of the microbiome in wheat grain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that stressed or injured cells could not be recovered in selective media and that cells present in low numbers are very often inhibited by other microbes (Hugenholtz et al, 1998). For these reasons, it is important to have methods that allow monitoring of the microbial populations without cultivation by culture-independent methods (Cocolin et al, 2004;Mangia et al, 2015). The culture-independent methods allowed us to confirm the dominant bacterial community of Karish cheeses that are almost identified in each sample "L. lactis subsp.…”
Section: The Diversity Of Lactic Acid Bacteria Using Ttge and Rep-pcrmentioning
confidence: 93%